2016
DOI: 10.1016/j.impact.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of the food matrix and gastrointestinal tract in the assessment of biological properties of ingested engineered nanomaterials (iENMs): State of the science and knowledge gaps

Abstract: Many foods contain appreciable levels of engineered nanomaterials (ENMs) (diameter < 100 nm) that may be either intentionally or unintentionally added. These ENMs vary considerably in their compositions, dimensions, morphologies, physicochemical properties, and biological responses. From a toxicological point of view, it is often convenient to classify ingested ENMs (iENMs) as being either inorganic (such as TiO2, SiO2, Fe2O3, or Ag) or organic (such as lipid, protein, or carbohydrate), since the former tend t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 153 publications
0
66
0
Order By: Relevance
“…6,109 Foodborne inorganic NPs are consumed as part of a food or beverage that may contain a variety of molecular and colloidal species that can interact with food nanoparticles and alter their biological fate. These interactions may occur within the food itself, or during the passage of the food nanoparticles through the GIT.…”
Section: Food Matrix and Git Effects On Nanoparticle Characteristics mentioning
confidence: 99%
“…6,109 Foodborne inorganic NPs are consumed as part of a food or beverage that may contain a variety of molecular and colloidal species that can interact with food nanoparticles and alter their biological fate. These interactions may occur within the food itself, or during the passage of the food nanoparticles through the GIT.…”
Section: Food Matrix and Git Effects On Nanoparticle Characteristics mentioning
confidence: 99%
“…It has already been shown that certain ENMs have the capacity to alter the bioavailability of nutrients [59] while others may increase the bioavailability of noxious agents, like pesticides. [57] In addition, food matrix effects have been shown to modulate the bioactivity of ENMs, [32,35] and the gut microbiome and proteome of animals is known to be sensitive to the presence of chemically active particulates. [28,29,60] Therefore, we plan to apply the methods developed here to interrogate the physicochemical transformations, toxicological assessment, and effect on gut microbiome and proteome of GO in the presence of more complex food models.…”
Section: In Vitro Toxicological Assessment Of Small Intestinal Go Digmentioning
confidence: 99%
“…These alterations include biodissolution, [33] biomolecular corona formation, [34] and morphological changes, like agglomeration. [35] In the case of anisotropic, carbonaceous, soft materials like GO, the technical challenges are ever so harder to overcome and could partially explain the scarcity in available literature.…”
Section: Introductionmentioning
confidence: 99%
“…Organic matter in the water column serves as an adsorption phase for graphene oxide. Ingested particles could also undergo transformation in the digestive tracts of these organisms (McClements et al 2016) and may further affect FIGURE 6: Total protein levels in gill and digestive gland tissues of graphene oxide-exposed oysters. In addition, organic material (feces and pseudofeces) from shelled mollusks could increase particle association in the water column.…”
Section: Graphene Oxide Exposure Assessmentmentioning
confidence: 99%
“…In natural environments, and as seen in our studies, nanomaterial aggregates can reach micron size ranges (Wong et al 2010;Sanchs et al 2015) that are preferred as food by bivalves and other coastal organisms. Ingested particles could also undergo transformation in the digestive tracts of these organisms (McClements et al 2016) and may further affect FIGURE 6: Total protein levels in gill and digestive gland tissues of graphene oxide-exposed oysters. Different letters indicate significant difference between concentrations; no letter indicates no difference.…”
Section: Graphene Oxide Exposure Assessmentmentioning
confidence: 99%